2015
DOI: 10.17576/gema-2015-1501-09
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of SOme Akan Personal Names

Abstract: This paper examines some morphophonological processes in Akan personal names with focus on the former process. The morphological processes of truncation of some indigenous personal names identified among the Akan (Asante) ethnic group of Ghana are discussed. The paper critically looks at some of these postlexical morpheme boundary processes in some Akan personal names realized in the truncated form when two personal names interact. In naming a child in a typical Akan, specifically in Asante"s custom, a family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Such sequence has been observed to be permitted in Akan personal names only at the juncture of two separate personal names said in a fast speech, and even that, such a sequence is as a result of compensatory lengthening (cf. Adomako 2015). This sequence can be of the same vowel quality, as in the examples above (under 'b-deletion'), or of two different qualities between the V1-and the remnant -V2V3 of the female morpheme.…”
Section: Reduction In the Female Morpheme -Baamentioning
confidence: 97%
See 1 more Smart Citation
“…Such sequence has been observed to be permitted in Akan personal names only at the juncture of two separate personal names said in a fast speech, and even that, such a sequence is as a result of compensatory lengthening (cf. Adomako 2015). This sequence can be of the same vowel quality, as in the examples above (under 'b-deletion'), or of two different qualities between the V1-and the remnant -V2V3 of the female morpheme.…”
Section: Reduction In the Female Morpheme -Baamentioning
confidence: 97%
“…Similarly, Agyekum (2006) also makes the same claim and in addition discusses other types of names such as event names, circumstantial names, birth number names, etc. Further references on the Akan naming practices are from Boadi (1984), Ansu-Kyeremeh (2000), Obeng (1997Obeng ( , 2001), Adomako (2015), among others. Brempong (1991) also talks briefly on this naming practice and the etymology of some Akan names including day-names; however, he fails to discuss the etymology of these names though he mentions them.…”
Section: Akan Naming Practicesmentioning
confidence: 99%
“…There have been enormous research on names from the perspectives of sociolinguistics (e.g. Egbewogbe, 1977;Agyekum, 2006;Abdul, 2014;Mensah, 2015), sociocultural (see Ansu-Kyeremeh, 2000;Dakubu, 2000;Dominic, 2014), pragmatics (see Obeng, 1998;Batoma, 2009;, morphophonology (Adomako, 2015;2017), morphosemantics (Olenyo, 2011;Jauro, et al, 2013;Gerba, 2014;Agyekum, 2018;Awukuvi and Israel, 2018), and morphosyntactic (cf. Mensah and Offong 2013;Jindayu, 2013).…”
Section: Related Literature: a Cross-linguistic Overviewmentioning
confidence: 99%
“…Addressing the morphophonology of personal names was also the focus of many papers. It is reported that personal names, for example, undergo some morphophonological alternations at the phonetic level of the language (Adomako 2015). Much research has also been devoted to studying the semantics associated with names (e.g., Lawson 1985;Garayevaa , Akhmetzyanova and Khismatullinaa 2016 ).…”
Section: Name and Identitymentioning
confidence: 99%